Analisis Kelainan Jantung Menggunakan Dimensi Fraktal Dan Transformasi Wavelet - Oktaviani, D R; Habiburrohman, M (Program Studi Matematika, Universitas Tadulako, 2020)
ABSTRACT The disease that causes the largest number of deaths in Indonesia to date is acute coronary syndrome or called the silence killer. Deaths due to coronary heart disease (CHD) reached 26.4%. Therefore, to prevent the high death rate from CHD, early detection of CHD can be done. One way that can be done is checking the ECG (electrocardiogram / electrocardiograph) record. Then by using the HRV (Heart Rate Variability) method, which is to analyze the ECG signal which can take measurements, physiological interpretation, and clinical use of the ECG signal so that it can find out an arrhythmia (a condition in which the heart beats erratically) a person's heart and take medical steps right. In this article using wavelet transform analysis to identify heart disease. The results are then compared with the fractal dimensions of the heart rate signal. FD identifies heart disease with more than 90% confidence Keywords : Fractal, Heart, Wavelet.